THE IMPLEMENTATION OF MULTI CRITERIA DECISION MAKING IN HANDLING CRIMINAL ACTIONS OF MARINE VIOLATION IN ALKI II AREA - Petrus Indra Cahyadi; Budisantoso Wirjodirdjo; Okol Sri Suharyo; Avando Bastari (JOURNAL ASRO, 2021)
One of the Main Duties of the Indonesian Navy (TNI AL) is to enforce the law and maintain security in the marine area of ​​national jurisdiction in accordance with the provisions of national law and international law which are then manifested in Marine Security Operations (Opskamla) The Indonesian Navy Base is one of the Opskamla components. which functions to project the strength of the Indonesian Navy to the area of ​​operation and provide ongoing administrative and logistical support to ensure the operational continuity of the elements of the Navy, carry out capacity building and conduct limited maritime security operations in the context of enforcing sovereignty and law at sea and carrying out coordination, regulation base defense. In the alternative selection of the Indonesian Navy Base in the Koarmada II work area, this study uses a combination of AHP and Topsis methods, the hierarchical structure modeling in the AHP method is influenced by the criteria and sub criteria, while for Topsis it is used as a ranking of the best alternative TNI AL bases as the initial position for Operation activities Marine Security The results obtained from the alternative weighting of the Indonesian Navy bases in sequence are the Banjarmasin Navy Base with a weight value of 0.959 more priority to be selected as a base for handling criminal offenses at sea, then the Nunukan Navy Base weight value 0.643 Palu weight value 0.589, Kendari weight value 0.333 Sangata has a weight value of 0.301, Kota Baru has a weight value of 0.265 and finally Toli-Toli has a weight value of 0.237. Keywords : Opskamla, Naval Base, Selection of bases, Indonesian Archipelago Sea Lanes (ALKI II), Analytical Hierarchy Process (AHP), Topsis.